“Evaluación de dos herbicidas biológicos en el control de malezas en corona en el cultivo de palma africana (Elaeis guineensis Jacq.)”. - Mawyin Alonzo, Johnny Raúl (2020)
African palm is a crop with a lot of demand for its industrial uses and as the new source of biofuel, which leads to adequate agronomic management mainly in its nutrition and weed control, evidencing the use of biological products for its management and control avoiding the chemists. The objective was to analyze the efficiency of biological herbicides in the control of broad and narrow leaf weeds in the African palm crown. It was carried out at Km 6 ½ via Buena Fe, in the months of March to July. A BCA design with a 2x3 + 2 factorial arrangement in 3 repetitions was used using an already established 7-year-old plantation. The factors studied were a) two biological herbicides and b) doses (1.0 L, 1.5 L and 2.0L), plus a chemical and a mechanical control with their interaction. The weed index before starting the study was statistically the same, the weeds that appeared in a higher percentage were the Poaceae, the weed control at 10 days the chemical control at 1.5 L was 20.00% higher than the best biological acid treatment Acetic + Eugenol + Carfentrazone in 2.0L. From 20 days the efficiency is balanced between T7 and the biological herbicides, being statistically equal in the doses of 1.5 and 2.0 L until the end of the evaluation at 120 DDA. The herbicide with the best performance was acetic acid + eugenol + carfentrazone at a dose of 2.0 L. The cost - efficiency ratio acetic acid + Eugenol in 1.5L obtained a lower treatment cost being the option for broadleaf weeds, the acid Acetic + Eugenol + Carfentrazone in 1.5L was indicated for broad and narrow leaf weeds. Keywords: African palm, weeds, control, biological herbicides, efficiency, cost.